2013
DOI: 10.1111/asj.12041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of D‐mannitol on nitrogen retention, fiber digestibility and digesta transit time in adult rabbits

Abstract: The aim of the current study was to elucidate the effect of gastrointestinal retention time of digesta on fiber digestibility in adult rabbits fed indigestible, but fermentable, sugar D-mannitol. Six adult rabbits were fed alternately a commercial diet containing 5% glucose and a diet containing D-mannitol. Total feces and urine were collected during the experimental period. Nitrogen (N) balance, digestibility of nutrients, and gastrointestinal mean retention time (MRT) were measured. The results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Moreover, the transit times (passage times) of bamboo in the digestive system of giant panda is reported to be short (on an average 8–10 h) (Dierenfeld et al, 1982 ; Schaller et al, 1985 ). It was remarkably faster than those of common herbivores, e.g., Wapiti (about 51 h) (Jiang and Hudson, 1996 ) and rabbit (approximately 61 h) (Min et al, 2013 ). Since the transit time of the food has been reported as the most critical factor to regulate the efficiency of consumed food utilization (Kotb and Luckey, 1972 ), considering such a rapid transit time and gut structure of giant panda, it is not surprising that it has low microbial fermentation efficiency for bamboo diet.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the transit times (passage times) of bamboo in the digestive system of giant panda is reported to be short (on an average 8–10 h) (Dierenfeld et al, 1982 ; Schaller et al, 1985 ). It was remarkably faster than those of common herbivores, e.g., Wapiti (about 51 h) (Jiang and Hudson, 1996 ) and rabbit (approximately 61 h) (Min et al, 2013 ). Since the transit time of the food has been reported as the most critical factor to regulate the efficiency of consumed food utilization (Kotb and Luckey, 1972 ), considering such a rapid transit time and gut structure of giant panda, it is not surprising that it has low microbial fermentation efficiency for bamboo diet.…”
Section: Discussionmentioning
confidence: 99%
“…In a small number of studies, the researchers found that iS supplementation also have similar promoting effects on mineral bioavailability in rabbits and other rodents except of rats. Dietary mannitol increased ash digestibility in adult rabbits [ 125 , 126 ]. A research by Kawasaki et al [ 10 ] showed that dietary FOS resulted in significantly higher ash digestibility in guinea pigs when compared with dietary glucose.…”
Section: Effects On Nutrient Digestion Absorption and Systemic Mmentioning
confidence: 99%
“…Taken together, D. melanogaster and its common microbes may be able to metabolize small amounts of mannitol, but likely not the amounts consumed in our experiment [48-51]. Mannitol may also slow down digestion [6], elevate carbohydrate ingestion to a detrimental degree [52], or have a dieuretic effect due to its slow absorption in the gut [53-54]. In flies, it is possible mannitol is transported into the hemolymph by aquaporins from the midgut [55], where it may lethally increase osmotic pressure like other sugar alcohols [56-57].…”
Section: Discussionmentioning
confidence: 99%
“…Mannitol produces a variety of gastrointestinal, reproductive, and survival effects when fed to other organisms [2,6-7]. Mannitol reduced survival and prevented adult female reproduction in Pimpla turionellae ichneumonid wasps [7].…”
Section: Introductionmentioning
confidence: 99%